Development of GIDI-SNAKE Media Based on Powtoon Animation Video on the Material of Formulation and Establishment of Pancasila to Improve Learning Achievement - Alik Ulfatus Solikah; Nuruddin Hady; Didik Sukriono (STAI Miftahul Ula Nganjuk, 2025)
This research aims to develop and test the effectiveness of the GIDI-SNAKE learning media based on Powtoon animation videos to address low learning achievement in seventh-grade students at SMP Negeri 1 Tugu, particularly in the topic of formulating and establishing Pancasila as the state ideology. The issue is exacerbated by the minimal use of innovative learning media by teachers. The ADDIE development model was applied to create a GIDI-SNAKE game board integrated with Powtoon videos. The game features question and information cards with barcodes, dice, pawns, and cue cards. The product was evaluated for validity, practicality, and effectiveness. The validity was confirmed with an average validation score of 3.84 from two media validators and 3.70 from the material validator. The practicality was demonstrated by a 94.7% approval rate from students. The effectiveness was validated by a significant improvement in learning outcomes, with pre-test and post-test scores of 41.29 and 85.23, respectively, and a significance value (sig) of 0.001, confirming the media’s effectiveness in improving student learning outcomes.